N2 fixation, and the relative contribution of fixed N, in corals from Curaçao and Hawaii - Michael P. Lesser; Kathleen M. Morrow; M. Sabrina Pankey (Coral Reefs, 2019)

Global community breaks at 60 m on mesophotic coral reefs - Michael P. Lesser; Marc Slattery; Jack H. Laverick; Keir J. Macartney; Tom C. Bridge (Global Ecology and Biogeography, 2019)
Aim Mesophotic coral ecosystems (MCEs) are unique communities that support a high proportion of depth‐endemic species distinct from shallow‐water coral reefs. However, there is currently little consensus on the boundaries between shallow and mesophotic coral reefs and between upper versus lower MCEs because studies of these communities are often site specific. Here, we examine the ecological evidence for community breaks, defined here as species loss, in fish and benthic taxa between shallow reefs and MCEs globally. Location Global MCEs. Time period 1973–2017. Major taxa studied Macrophytes, Porifera, Scleractinia, Hydrozoa, Octocorallia, Antipatharia and teleost fishes. Methods We used random‐effects models and breakpoint analyses on presence/absence data to identify regions of higher than expected species loss along a depth gradient of 1–69 m, based on a meta‐analysis of 26 studies spanning diverse photoautotrophic and heterotrophic taxa. We then investigated the extent to which points of high faunal turnover can be explained by environmental factors, including light, temperature and nutrient availability. Results We found evidence for a community break, indicated by a significant loss of shallow‐water taxa, at ~ 60 m across several taxonomically and functionally diverse benthic groups and geographical regions. The breakpoint in benthic composition is best explained by decreasing light, which is correlated with the optical depths between 10 and 1% of surface irradiance. A concurrent shift in the availability of nutrients, both dissolved and particulate organic matter, and a shift from photoautotroph to heterotroph‐dominated assemblages also occurs at ~ 60 m depth. Main conclusions We found evidence for global community breaks across multiple benthic taxa at ~ 60 m depth, indicative of distinct community transitions between shallow and mesophotic coral ecosystems. Changes in the underwater light environment and the availability of trophic resources along the depth gradient are the most parsimonious explanations for the observed patterns.

Phylogenetic signature of light and thermal stress for the endosymbiotic dinoflagellates of corals (Family Symbiodiniaceae) - Michael P. Lesser (Limnology and Oceanography, 2019)
Coral reefs around the world have been affected by a climate‐change induced phenomenon known as “coral bleaching,” which is caused by the interaction between high irradiance and elevated seawater temperatures, and involves the mass expulsion of Symbiodiniaceae from anemones, sponges, and corals. The primary drivers of this phenomenon are the inherent genetic variability in the Family Symbiodiniaceae, and the variability in the abiotic environment for variables such as irradiance and temperature. Recent experiments have either disregarded the important interactive role of irradiance or have suggested that photooxidative stress is not a prerequisite for coral bleaching because certain reactive oxygen species (ROS) can be produced in the dark. Here, fluorescent probes are used as proxies for the relative concentration of ROS in different genera of cultured Symbiodiniaceae under varying thermal and light conditions. The results show that taxon‐specific patterns of the concentration of ROS are observed but that all genera tested produced significantly greater amounts of superoxide radicals and hydrogen peroxide, compared to singlet oxygen, when exposed to high light and thermal stress. These results are contextualized in relation to the primary drivers of ROS production and the photo‐physiological basis for differences in ROS production that may then be correlated with symbiont driven coral bleaching.